Plant odorants interfere with detection of sex pheromone signals by male Heliothis virescens - Pregitzer, Pablo; Schubert, Marco; Breer, Heinz; Hansson, Bill S.; Sachse, Silke; Krieger, Jürgen (Frontiers in Cellular Neuroscience, 2012)
In many insects, mate finding relies on female-released sex pheromones, which have to be deciphered by the male olfactory system within an odorous background of plant volatiles present in the environment of a calling female. With respect to pheromone-mediated mate localization, plant odorants may be neutral, favorable or disturbing. Here we examined the impact of plant odorants on detection and coding of the major sex pheromone component, (Z)-11-hexadecenal (Z11-16:Ald) in the noctuid moth Heliothis virescens. By in vivo imaging the activity in the male antennal lobe, we monitored the interference at the level of olfactory sensory neurons (OSN) to illuminate mixture interactions. The results show that stimulating the male antenna with Z11-16:Ald and distinct plant-related odorants simultaneously suppressed pheromone-evoked activity in the region of the macroglomerular complex (MGC), where Z11-16:Ald-specific OSNs terminate. Based on our previous findings that antennal detection of Z11-16:Ald involves an interplay of the pheromone binding protein HvirPBP2 and the pheromone receptor HR13, we asked if the plant odorants may interfere with any of the elements involved in pheromone detection. Using a competitive fluorescence binding assay, we found that the plant odorants neither bind to HvirPBP2 nor affect the binding of Z11-16:Ald to the protein. However, imaging experiments analyzing a cell line that expressed the receptor HR13 revealed that plant odorants significantly inhibited the Z11-16:Ald-evoked calcium responses. Together the results indicate that, plant odorants can interfere with the signaling process of the major sex pheromone component at the receptor level. Consequently, it can be assumed that plant odorants in the environment may reduce the firing activity of pheromone-specific OSNs in H. virescens and thus affect mate localization.